2014
DOI: 10.1007/s13193-014-0322-7
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic Debulking Followed by Bronchoplastic Procedure Helps in Limiting Lung Resection in a Bronchial Carcinoid: A Case Report

Abstract: Bronchoplasty is a conservative procedure in lung surgeries used in the past for patients with poor functional status but recently these procedures have been performed in low grade malignant tumors of lung avoiding extensive morbid procedure like pneumonectomy without compromising the oncologic outcome. We describe a case of bronchial carcinoid treated by bronchoscopic intervention followed by wedge bronchoplasty. The importance of bronchoscopic debulking of the tumor for accurate assessment of its extent has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Following bronchoscopic snaring of the polypoidal component of the tumor, the true extent of the tumor could be accurately defined, pneumonia resolved, and he underwent right upper lobectomy with wedge bronchoplasty. [18] Anatomical lung resection with preservation of functional lung parenchyma (lobectomy or sleeve resection/bronchoplastic procedure) is the treatment of choice, and every effort should be made to preserve functional lung. [13,16] Pneumonectomy should be avoided whenever possible; however, it may be necessary in cases where the distal lung parenchyma is destroyed due to long-standing obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Following bronchoscopic snaring of the polypoidal component of the tumor, the true extent of the tumor could be accurately defined, pneumonia resolved, and he underwent right upper lobectomy with wedge bronchoplasty. [18] Anatomical lung resection with preservation of functional lung parenchyma (lobectomy or sleeve resection/bronchoplastic procedure) is the treatment of choice, and every effort should be made to preserve functional lung. [13,16] Pneumonectomy should be avoided whenever possible; however, it may be necessary in cases where the distal lung parenchyma is destroyed due to long-standing obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] Distant Metastasis at presentation is rare in PSGTTL. None of our patient had distant metastasis at presentation.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…The clinicodemographic profile of cases and types of bronchoscopic intervention including outcome of treatment has been described in Supplementary Tables and , respectively. [ 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ] Various bronchoscopic treatment options as mentioned in these studies were practiced depending on the physician's discretion, expertise, and available resources. All studies have reported high success rates with minimal complications and good long-term outcome.…”
Section: Discussionmentioning
confidence: 99%